Click-chemistry-derived tetracycline-amino acid conjugates exhibiting exceptional potency and exclusive recognition of the reverse tet repressor - Usai, Igor; Krüger, Marcus; Einsiedel, Jürgen; Hillen, Wolfgang; Gmeiner, Peter (ChemBioChem, 2010)
A click-chemistry-based synthesis of biologically active doxycycline-amino acid conjugates is described. Starting from 9-aminodoxycycline derivatives and complementary functionalized amino acids, ligation was accomplished by copper(I)-catalyzed azide-alkyne [3+2] cycloaddition (CuAAC). The final products were tested in a variety of TetR and revTetR systems, and the C-terminally linked phenylalanine conjugate 12c exhibited high selectivity for revTetR over TetR. Besides the unique property of the specific effector 12c to effectively differentiate TetR and its reverse phenotype, the test compound proved to be almost devoid of any antibacterial activity; this will be highly beneficial for future applications to control gene expression in bacterial systems. © 2010 Wiley-VCH Verlag GmbH& Co. KGaA.